2012
DOI: 10.1038/pj.2012.11
|View full text |Cite
|
Sign up to set email alerts
|

Chitin-chitosan nanocomposite gels: reinforcement of chitosan hydrogels with rod-like chitin nanowhiskers

Abstract: Nanocomposite gels containing chitosan as a network polymer and chitin nanowhiskers as reinforcing fillers were prepared by cross-linking with the blocked isocyanate hexamethylene-1,6-di-(aminocarboxysulfonate) (HDS). Young's modulus and stress at break of the nanocomposite gels increased to maximum values of 169 and 135 kPa, respectively, with increase in whisker content up to 13.3%, whereas the degree of swelling decreased from 357 to 33.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 37 publications
4
81
0
Order By: Relevance
“…CMC (degree of polymerization n = 500, Tokyo Chemical Industry Co, Ltd, Tokyo, Japan), HPC (150–400 cP at 20 g/l at 20°C, Wako Pure Chemical Industries, Osaka, Japan) and chitosan (Daichitosan PVL, molecular weight 5–20 × 10 4 g/mol, Dainichiseika Color & Chemicals Mfg Co, Ltd, Tokyo, Japan) were used as received. Degree of deacetylation of the used chitosan was found to be 83% by colloidal titration . All other chemicals were purchased from Wako Pure Chemical Industries (Osaka, Japan) and used without further purification unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CMC (degree of polymerization n = 500, Tokyo Chemical Industry Co, Ltd, Tokyo, Japan), HPC (150–400 cP at 20 g/l at 20°C, Wako Pure Chemical Industries, Osaka, Japan) and chitosan (Daichitosan PVL, molecular weight 5–20 × 10 4 g/mol, Dainichiseika Color & Chemicals Mfg Co, Ltd, Tokyo, Japan) were used as received. Degree of deacetylation of the used chitosan was found to be 83% by colloidal titration . All other chemicals were purchased from Wako Pure Chemical Industries (Osaka, Japan) and used without further purification unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
“…Chitin nanowhiskers/chitosan nanocomposite gels were prepared essentially by following our previous study, using a crosslinker HDS that was synthesized according to the method by Welsh et al . Briefly, 2 g of chitosan powders was well dissolved in 20 g of 5 wt.% aqueous acetic acid solution by magnetic stirring, followed by removal of trace insolubles by filtration or decantation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanofibrillar chitin hydrogels are biodegradable, biocompatible, and nontoxic, and thus show promise for biomedical applications. The protonation of amino groups on the surface of chitin allows its application in wound dressings due to the antimicrobial properties of cationic gels [130]. Polymeric fibers that mimic the structure and function of the extracellular matrix are also of interest in tissue engineering and cell culture.…”
Section: Polysaccharide Gelsmentioning
confidence: 99%
“…Among the used reinforcing materials, polysaccharide nanocrystals (nanowhisker), such as cellulose [1,2], starch [3][4][5], and chitin nanocrystals [6][7][8][9][10][11][12], show great potential to improve the polymer's mechanical properties, thermal stability, and solvent responsibility without significant affecting the transparency. Many studies have shown that incorporating a small amount (1-10 %) of these nanocrystals into polymers can induce vast improvement in properties [1,13].…”
Section: Introductionmentioning
confidence: 99%